2017
DOI: 10.1002/adfm.201605598
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Spin Dynamics via Voltage Control of Spin‐Lattice Coupling in Multiferroics

Abstract: Motivated by the most recent progresses in both magnonics (spin dynamics) and multiferroics fields, this work aims at magnonics manipulation by the magnetoelectric coupling effect. Here, voltage control of magnonics, particularly the surface spin waves, is achieved in La0.7Sr0.3MnO3/0.7Pb(Mg1/3Nb2/3)O3‐0.3PbTiO3 multiferroic heterostructures. With the electron spin resonance method, a large 135 Oe shift of surface spin wave resonance (≈7 times greater than conventional voltage‐induced ferromagnetic resonance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…This flaw extremely limits their deployments in portable devices . As an alternative, electric field (E‐field) control of magnetism is more promising toward fast, compact, and light‐weighted devices . Nevertheless, the strain/stress‐mediated magnetoelectric coupling in conventional ferromagnetic (FM)/ferroelectric multiferroic heterostructures can hardly be effective on soft substrates.…”
mentioning
confidence: 99%
“…This flaw extremely limits their deployments in portable devices . As an alternative, electric field (E‐field) control of magnetism is more promising toward fast, compact, and light‐weighted devices . Nevertheless, the strain/stress‐mediated magnetoelectric coupling in conventional ferromagnetic (FM)/ferroelectric multiferroic heterostructures can hardly be effective on soft substrates.…”
mentioning
confidence: 99%
“…Nagaoka et al 18 have shown that the frequency of propagating SWs in FM films possessing iPMA can be modulated by VCMA without charge current. Although there are some reports about the electric-field modulation of SWs in multiferroic materials 27,28 and ferrimagnetic insulators (e.g. YIG) 82,86 , the VCMA modulation of SWs in metallic FMs has several advantages over them as already discussed.…”
Section: Reconfigurable Magnonic Crystalsmentioning
confidence: 99%
“…Magnetoelectric (ME) effect allows us to control magnetic properties by electric field. Multiferroic materials show strong ME effect due to presence of magnetic and electrical ordering, simultaneously 27,28 . The strong coupling between magnetic and electric polarization allows to control magnetic properties by electric field and vice versa.…”
mentioning
confidence: 99%
“…[1] Zhu et al innovated a voltage control two spin wave logic states in La 0.7 Sr 0.3 MnO 3 (LSMO)/0.7Pb(Mg 1/3 Nb 2/3 ) O 3 -0.3PbTiO 3 (PMN-PT) heterostructure via interfacial spin-lattice coupling. [2] Here, LSMO is an ideal coupling system by the degrees of charge, lattice, orbital, spin, and their strong interactions. [1,2,[19][20][21][22][23] The strain of the polarized substrate deformed the lattice of LSMO, and the variation of the boundary condition emitted or vanished the body spin wave realizing an "on/off" two-logic switching.…”
mentioning
confidence: 99%
“…[2] Here, LSMO is an ideal coupling system by the degrees of charge, lattice, orbital, spin, and their strong interactions. [1,2,[19][20][21][22][23] The strain of the polarized substrate deformed the lattice of LSMO, and the variation of the boundary condition emitted or vanished the body spin wave realizing an "on/off" two-logic switching. [2,24] Nevertheless, the strain-mediated spin wave manipulation usually requires hundreds of volts to acquire a high electrostriction of the piezoelectric substrate.…”
mentioning
confidence: 99%